MicroRNA Let-7 targets AMPK and impairs hepatic lipid metabolism in offspring of maternal obese pregnancies - Simino, Laís A. P. (Sci Rep, 2021)
Nutritional status during gestation may lead to a phenomenon known as metabolic programming, which can be triggered by epigenetic mechanisms. The Let-7 family of microRNAs were one of the first to be discovered, and are closely related to metabolic processes. Bioinformatic analysis revealed that Prkaa2, the gene that encodes AMPK α2, is a predicted target of Let-7. Here we aimed to investigate whether Let-7 has a role in AMPKα2 levels in the NAFLD development in the offspring programmed by maternal obesity. Let-7 levels were upregulated in the liver of newborn mice from obese dams, while the levels of Prkaa2 were downregulated. Let-7 levels strongly correlated with serum glucose, insulin and NEFA, and in vitro treatment of AML12 with glucose and NEFA lead to higher Let-7 expression. Transfection of Let-7a mimic lead to downregulation of AMPKα2 levels, while the transfection with Let-7a inhibitor impaired both NEFA-mediated reduction of Prkaa2 levels and the fat accumulation driven by NEFA. The transfection of Let-7a inhibitor in ex-vivo liver slices from the offspring of obese dams restored phospho-AMPKα2 levels. In summary, Let-7a appears to regulate hepatic AMPKα2 protein levels and lead to the early hepatic metabolic disturbances in the offspring of obese dams.